The Effect of Work Load and Quality Work Life on the Performance Of Police Members in Indonesian Police Headquarters Korlantas with Job Satisfaction as Intervening Variables - Siska Wirastuti; I Ketut R; Henry Eryanto; Juhasdi Susono; Amiruddin K (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2020)
This article aims to determine the influence of workload and quality of work life on the performance of police officers at Korlantas Police Headquarters with job satisfaction as an intervening variable. The research sample was 249 police officers at Korlantas Mabes indonesian police. The sample selection method uses probability sampling techniques. Data were collected by distributing questionnaires. The questionnaire used was tested for validity and reliability first, before entering the further analysis stage. Analysis of research data using SEM (Structural Equation Modeling) with processing program AMOS software. The results showed that workload has no effect on job satisfaction and work performance while quality work of life has positive and significant effect on job satisfaction and work performance. Meanwhile, job satisfaction has positive and significant effect on job performance. Job satisfaction has no mediating effect on the relationship between workload and performance of temporary employees job satisfaction was found have a mediating effect on the relationship between quality work of life and employee performance. Keywords : Workload, Job Satisfaction, Performance, Quality Work Life